Effects of L-Serine and L-Proline on Crystallization Kinetics of Calcium Pyrophosphate Dihydrate - SAYAN, PERVİZ; SARGUT, SİBEL (WILEY-V C H VERLAG GMBH, 2018)
Calcium pyrophosphate dihydrate (CPPD) crystallization was investigated in a mixed-suspension mixed-product removal (MSMPR)-type crystallizer in the presence of the amino acids L-serine and L-proline as additives. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and zeta potential analysis were applied for characterization of the crystals obtained. CPPD crystals obtained in pure media consisted of aggregated particles which included plate-like structures and rod-shaped crystals. However, it was observed that agglomeration and breakage tendency on CPPD crystals obtained in the presence of amino acids were remarkable. The population balance equation for CPPD crystals was resolved with numerical analysis considering aggregation and breakage steps. The predominant mechanism was the breakage for CPPD crystallization in the presence of amino acids.
Keywords: Agglomeration; Amino acids; Breakage; Calcium pyrophosphate dihydrate; Crystallization kinetics; ARTICULAR-CARTILAGE; CRYSTALS; GROWTH